Les domaines linguistiques de la subjectivité du locuteur: étude empirique avec données de corpus - Grisot, Cristina (Travaux neuchâtelois de linguistique, 2019)
In this article we report the results of an empirical study with corpus data targeting the identification of the linguistic domains of the speaker's subjectivity – broadly understood as referring to the expression of the speaker's perspective, emotions and attitudes. In order to attain this aim, we carried out an annotation study on corpus data (randomly selected from a literary text and from a journalistic text), formulated hypotheses on the basis of the state of the research and analysed the data with respect to three variables: the register, the source of subjectivity (speaker or third party) and the types of linguistic cues indicating the speaker's subjectivity. Our quantitative analyses showed that (i) the register does not influence the expression of subjectivity, (ii) the main linguistic domains of subjectivity are the affective-evaluative lexicon and syntactic structures, (iii) that deictic subjectivity is in fact non-subjective and that speaker's subjectivity refers only to affective-evaluative subjectivity. More generally, this article makes a methodological contribution about how to study an almost ineffable phenomenon, speaker's subjectivity, in a neutral and empirical manner.